Patient-Reported Satisfaction with a Novel, Tele-Optometric Comprehensive Eye Exam. - Patel, Jaymeni; Morettin, Christina E.; Wyles, Elizabeth; Fazio, Kimberly; Randhawa, Harneet K.; Messner, Leonard V. (Optometry & Visual Performance, 2023)
Background: Technology is becoming a pivotal component of day-to-day tasks, and its implementation in healthcare must be thoroughly investigated. This study aimed to compare the DigitalOptometrics tele-optometric examination experience to the traditional inperson comprehensive eye examination with post-examination satisfaction surveys. Methods: This study included 30 optometry students who were enrolled at the Illinois College of Optometry (ICO). Participants with active ocular pathology or a history of ocular surgery in the past 90 days were excluded. A teleoptometric comprehensive eye examination via the DigitalOptometrics platform was performed, and participants were provided with a postexamination survey. This was followed by an inperson comprehensive eye examination, and participants were provided with the same postexamination survey. After the completion of both examinations, participants were asked to complete a final satisfaction survey comparing the examinations. Results: Statistical analysis using Fisher analysis concluded that patient-reported satisfaction for the DigitalOptometrics tele-optometric examination was comparable to that for the gold-standard, inperson comprehensive eye examination. Conclusions: Our data suggests that the initial reported patient satisfaction was positive or comparable to that for an in-person comprehensive eye examination, supporting our hypothesis.